عبد القادر الجيلاني وأثره في التصوف المغاربي - بلول, العيد; بلول, عبدالك; مولى, سعد (جامعة الوادي - University of Eloued, 2023)
يعتبر الشيخ عبد القادر الجيلاني من أعظم مشايخ زمانه ، فقد اشتهر بعلمه و ورعه و فقهه و تصوفه ، و مما زاد في شهرته تأسيسه للطريقة القادرية التي تعد من أقدم الطرق الصوفية التي ظهرت في العالم الإسلامي ، و التي انتشرت في معظم الأقطار الإسلامية ، و يرجع الفضل في ذلك إلى أبناءه و تلاميذه و أتباعه الذين توزعوا في مناطق متعددة من الأقطار الإسلامية ، و انتشرت هذه الطريقة في بلاد المغرب الإسلامي بفضل ولديه الشيخين عبد العزيز و إبراهيم ، و كذلك الشيخ أبي مدين شعيب الذي أخذ أسس الطريقة القادرية من الشيخ عبد القادر الجيلاني الذي التقاه في الحج حسب المصادر التي ترجمت للشيخين ، و بفضل جهود أبي مدين و جهود تلاميذه و أتباعه انتشرت بشكل واسع لتشمل أغلب بقاع المغرب الإسلامي .Sheikh Abd al-Qadir al-Jilani is considered one of the greatest sheikhs of his time. He was famous for his knowledge, piety, jurisprudence, and Sufism, and what increased his fame was his establishment of the Qadiriya method, which is one of the oldest Sufi orders that appeared in the Islamic world, and which spread in most Islamic countries. The credit for this goes to his sons, students, and followers who were distributed in various regions of the Islamic countries, and this method spread in the countries of the Islamic Maghreb thanks to his two sons, Sheikh Abd al-Aziz and Ibrahim, as well as Sheikh Abu MadinShuaib, who took the foundations of the Qadiri method from Sheikh Abd al-Qadir al-Jilani Which he met during the pilgrimage according to the sources that were translated by the two sheikhs, and thanks to the efforts of Abu Madian and the efforts of his students and followers, it spread widely to include most parts of the Islamic Maghreb.
مذكرة ماستر تاريخ المغرب الاسلامي وسيط
Keywords: عبد القادر الجيلاني – التصوف المغاربي – بلاد المشرق – بلاد المغرب الاسلامي – ابي مدين شعيب; Abd al-Qadir al-Jilani - Maghreb Sufism - the countries of the East - the countries of the Islamic Maghreb - AbiMadianShuaib